Predictors of depressive symptoms in women at the beginning of thyroid cancer treatment (Research, Society and Development, 2022)
This study aims to analyze the correlation of levels of anxiety symptoms, spiritual well-being and social support with depressive symptoms, building a predictor model of depression for women with thyroid cancer at the beginning of treatment. The interviews were conducted with women who started treatment against thyroid cancer at the oncology referral hospital in Sergipe (2017-2018), where socioeconomic and clinical data were collected and symptoms of depression, anxiety, level of spiritual and well-being were evaluated. of social support through validated instruments. Sixty-six women with a mean age of 48 years were included in the survey. Participants had mild symptoms of anxiety and depression, mean 12.71 and 8.38, respectively. For spiritual well-being, the average was 103.64 and social support, an average of 59.48, indicating high scores. There was a strong correlation of symptoms of anxiety and depression and an inverse correlation of the level of spiritual well-being and social support with symptoms of depression. It was observed that symptoms of anxiety, spiritual well-being and social support are predictors of depressive symptoms in women with thyroid cancer at the beginning of treatment. Therefore, health professionals must treat cancer patients in their entirety, through a humanized and effective conduct.